Aerogel composite material, preparation method thereof and thermal insulation material

Through modification treatment and irradiation crosslinking technology, an efficient aerogel composite material is formed, which solves the problems of powder loss, poor toughness and poor hydrophobicity of traditional silica aerogel felt, and achieves high thermal insulation, superhydrophobicity and excellent toughness.

CN119822784APending Publication Date: 2025-04-15GUANGDONG ALISON HI TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510150333.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional silica aerogel felts have problems such as powder loss, poor toughness and poor hydrophobicity.

Method used

The aging treatment was performed by mixing the silicon sol and the fiber felt, and the modification treatment was made with a hydrophobic agent to form an acrylate protective layer, and a dense three-dimensional network structure was formed by irradiation cross-linking treatment.

Benefits of technology

It improves the hydrophobic properties and toughness of aerogel composite materials, avoids the shedding of aerogel powder, and enhances its thermal insulation performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of heat insulation and heat preservation materials, in particular to an aerogel composite material, a preparation method thereof and a heat insulation and heat preservation material. The preparation method of the aerogel composite material comprises the following steps: mixing silica sol and a fiber felt, and carrying out aging treatment to obtain a wet gel felt; carrying out modification treatment on the wet gel felt by utilizing a water repellent agent to obtain a modified gel felt; forming a protective layer on the modified gel felt by using acrylate to obtain a composite gel felt; and carrying out irradiation crosslinking treatment on the composite gel felt, and drying to obtain the aerogel composite material. The preparation method provided by the invention is simple and easy to implement, the obtained aerogel composite material has high heat insulation property, super-hydrophobicity, good powder falling resistance and excellent toughness, the overall stability and the use performance are remarkably improved, and the aerogel composite material is safer and more reliable in practical application and has wide application prospects. The requirements of the market on environment-friendly and high-performance heat insulation materials can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal insulation materials, and in particular to an aerogel composite material, a preparation method thereof, and a thermal insulation material. Background Art

[0002] As an emerging super insulation material, silica aerogel provides thermal insulation effects that other materials cannot match due to its extremely low thermal conductivity. In addition, it also has the advantages of low density, waterproof and flame retardant, green and environmentally friendly, corrosion-resistant, not easy to age and long service life. Therefore, silica aerogel is widely used in thermal insulation in industrial pipelines, furnaces, lifeboats, transportation, household appliances, glass and other fields. However, due to the brittleness of the silicon-oxygen bond and the hydrophilicity of the silicon hydroxyl group, traditional silica aerogel felt still has problems such as powder loss, poor toughness and poor hydrophobicity. Summary of the invention

[0003] Based on this, it is necessary to provide an aerogel composite material and a preparation method thereof and a thermal insulation material to solve the problems of traditional silica aerogel felt such as powder shedding, poor toughness and poor hydrophobicity.

[0004] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0005] In a first aspect of the present application, a method for preparing an aerogel composite material is provided, comprising the following steps:

[0006] Mixing silica sol and fiber felt, and performing aging treatment to obtain wet gel felt;

[0007] Modifying the wet gel felt by using a hydrophobic agent to obtain a modified gel felt;

[0008] forming a protective layer on the modified gel felt using acrylic acid to obtain a composite gel felt;

[0009] The composite gel felt is subjected to radiation cross-linking treatment and dried to obtain the aerogel composite material.

[0010] In some embodiments, the hydrophobic agent includes at least one of vinyltrichlorosilane, allyltrichlorosilane, 2-butenyltrichlorosilane, 5-hexenylmethyldichlorosilane, and 7-octenyltrichlorosilane.

[0011] In some embodiments, the acrylate includes at least one of methyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol tetraacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene glycol dimethacrylate, and trimethylolpropane triacrylate.

[0012] In some embodiments, the wet gel felt is modified by using a hydrophobic agent, comprising the following steps: placing the wet gel felt in a first mixed solution containing the hydrophobic agent for soaking.

[0013] In some embodiments, the mass fraction of the hydrophobic agent in the first mixed liquid is 5% to 40%.

[0014] In some embodiments, the solvent of the first mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane.

[0015] In some embodiments, the soaking treatment conditions include: soaking at 25°C to 70°C for 12h to 72h.

[0016] In some embodiments, forming a protective layer on the modified gel felt using acrylate includes the following steps: spraying the modified gel felt with a second mixed liquid containing the acrylate to form a protective layer.

[0017] In some embodiments, the mass fraction of the acrylic acid ester in the second mixed liquid is 3% to 40%.

[0018] In some embodiments, the solvent of the second mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane.

[0019] In some embodiments, the protective layer has a thickness of 10 μm to 3000 μm.

[0020] In some embodiments, the silica sol and the fiber felt are mixed and subjected to an aging reaction, comprising the following steps:

[0021] Mixing a silicon source, an organic solvent and water, and performing a hydrolysis reaction and a polycondensation reaction to obtain the silica sol;

[0022] The silica sol and the fiber felt are placed in an aging solution containing a silicon source and allowed to stand for aging.

[0023] In a second aspect of the present application, an aerogel composite material is provided, which is prepared by the above-mentioned preparation method of the aerogel composite material.

[0024] In a third aspect of the present application, a thermal insulation material is provided, comprising the above-mentioned aerogel composite material.

[0025] This application has at least the following beneficial effects:

[0026] The present application uses a hydrophobic agent to hydrophobically modify the wet gel felt, and uses acrylate as a protective layer. During the irradiation cross-linking treatment, the acrylates undergo a cross-linking curing reaction, thereby forming a dense three-dimensional network structure on the surface of the gel, which not only improves the hydrophobicity of the aerogel composite material, but also effectively avoids the shedding of aerogel powder and increases the toughness of the aerogel composite material. The preparation method provided by the present application is simple and easy, and the obtained aerogel composite material has high thermal insulation, super hydrophobicity, good anti-powdering performance and excellent toughness, and the overall stability and use performance are significantly improved. It is safer and more reliable in practical applications, and can meet the market demand for green, environmentally friendly and high-performance thermal insulation materials. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0029] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0030] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0031] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0033] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0034] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0035] the term

[0036] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0037] "Alkenyl" refers to a group containing at least one unsaturated site, i.e., a carbon-carbon sp 2 A monovalent residue formed by a hydrogen atom of a hydrocarbon with a double bond, a secondary carbon atom, a tertiary carbon atom or a ring carbon atom. Suitable examples include, but are not limited to, vinyl (-CH=CH2), allyl (-CH2CH=CH2), cyclopentenyl (-C5H7), 5-hexenyl (-CH2CH2CH2CH2CH=CH2).

[0038] Rational use of energy and energy conservation are of great significance to the sustainable development of the economy. Using new technologies and processes to develop environmentally friendly thermal insulation materials is one of the most effective and economical measures to save energy, which can not only reduce energy consumption, but also reduce environmental burden and promote green development.

[0039] Aerogel felt is a composite material made of fiber felt and aerogel, and its structural strength is higher than that of aerogel material alone. Generally, after the aerogel felt is dried, the colloid and matrix of some small particles are not firmly bonded, and under vibration, the aerogel particles fall off from the fiber matrix. Therefore, during the transportation, construction and use of aerogel felt, there is a common problem of aerogel powder falling off, which not only brings inconvenience to the construction, but also may threaten the health of the construction workers and reduce the thermal insulation performance of the aerogel felt. Therefore, under the premise of ensuring the good thermal insulation performance of the aerogel felt, it is very necessary to develop an aerogel composite material that does not fall off, in order to protect the health of production personnel and users, while meeting various market needs.

[0040] At present, the common anti-powdering scheme is to use glass fiber cloth, aluminum foil cloth and other materials to apply on the surface of aerogel felt. However, this method often has high labor costs and is not conducive to large-scale production. At the same time, in the process of cutting aerogel felt, aerogel powder may still fall off the felt. In addition, once applied, the flexibility of the material is reduced, resulting in difficulty in curling and bending, thereby affecting the convenience of storage and transportation and construction and installation. Therefore, it is of great significance to prepare silica aerogel composite materials with superhydrophobic, anti-powdering and toughening properties, which can effectively improve the performance of aerogel felt and enhance its operability and safety in various applications.

[0041] Based on this, the first aspect of the present application provides a method for preparing an aerogel composite material.

[0042] In some embodiments, the method for preparing the aerogel composite material comprises the following steps:

[0043] S100: mixing silica sol and fiber felt, performing aging reaction, and obtaining wet gel felt;

[0044] S200: modifying the wet gel felt using a hydrophobic agent to obtain a modified gel felt;

[0045] S300: using acrylic acid ester to form a protective layer on the modified gel felt to obtain a composite gel felt;

[0046] S400: performing radiation cross-linking treatment on the composite gel felt, and obtaining an aerogel composite material after drying.

[0047] The present application uses a hydrophobic agent to hydrophobically modify the wet gel felt, and uses acrylate as a protective layer. During the irradiation cross-linking treatment, the acrylates undergo a cross-linking curing reaction, thereby forming a dense three-dimensional network structure on the surface of the gel, which not only improves the hydrophobicity of the aerogel composite material, but also effectively avoids the shedding of aerogel powder and increases the toughness of the aerogel composite material. The preparation method provided by the present application is simple and easy, and the obtained aerogel composite material has high thermal insulation, super hydrophobicity, good anti-powdering performance and excellent toughness, and the overall stability and use performance are significantly improved. It is safer and more reliable in practical applications, and can meet the market demand for green, environmentally friendly and high-performance thermal insulation materials.

[0048] The preparation method of the aerogel composite material is described in detail below in a step-by-step manner.

[0049] S100: Mix silica sol and fiber felt, perform aging reaction, and obtain wet gel felt.

[0050] In some embodiments, the fiber felt includes at least one of glass fiber felt, aluminum silicate fiber felt, quartz fiber felt, high silica fiber felt, carbon fiber felt, pre-oxidized silk fiber felt, mullite fiber felt, basalt fiber felt, silicon carbide fiber felt, alumina fiber felt and boron nitride fiber felt.

[0051] The above-mentioned fiber felt has unique physical and chemical properties and plays an important role in the fields of high temperature resistance, heat insulation, insulation or reinforcement materials. Suitable fiber felt can be selected according to specific application requirements to improve the performance and stability of aerogel composite materials.

[0052] In some embodiments, the method for preparing silica sol comprises the following steps: mixing a silicon source, an organic solvent and water, and performing a hydrolysis reaction and a polycondensation reaction to obtain silica sol.

[0053] In some embodiments, the molar ratio of the silicon source, the organic solvent and the water is 1:(2-4):(9-16). As an example, the molar ratio of the silicon source to the organic solvent includes but is not limited to 1:2, 1:2.5, 1:3, 1:3.5 or 1:4, and the molar ratio of the silicon source to water includes but is not limited to 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 or 1:16.

[0054] In some embodiments, the silicon source includes at least one of tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), butyl orthosilicate (TBOS), and isopropyl orthosilicate (TIOS).

[0055] In some embodiments, the organic solvent includes at least one of methanol, ethanol, isopropanol and acetone. Further, the organic solvent can be ethanol, such as anhydrous ethanol with a water content of less than 5%.

[0056] In some embodiments, the pH of the hydrolysis reaction is 2 to 6. As an example, the pH of the hydrolysis reaction includes, but is not limited to, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 or 6.

[0057] In some embodiments, the hydrolysis reaction is carried out under the action of an acidic catalyst, and the acidic catalyst includes at least one of an inorganic acid and an organic acid. The inorganic acid includes at least one of nitric acid, sulfuric acid and nitric acid, and the organic acid includes at least one of formic acid, acetic acid, oxalic acid and tartaric acid.

[0058] In some embodiments, the hydrolysis reaction time is 0.5 h to 4 h. As an example, the hydrolysis reaction time includes but is not limited to 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0059] In some embodiments, the pH of the polycondensation reaction is 7 to 10. As an example, the pH of the polycondensation reaction includes, but is not limited to, 7, 7.5, 8, 8.5, 9, 9.5, or 10.

[0060] In some embodiments, the polycondensation reaction is carried out under the action of an alkaline catalyst, and the alkaline catalyst includes at least one of sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), tetramethylammonium hydroxide (TMAH), ammonia water (NH3·H2O) and barium hydroxide (Ba(OH)2). Further, the alkaline catalyst can be ammonia water.

[0061] In some embodiments, the silica sol and the fiber felt are mixed and subjected to an aging reaction, comprising the following steps:

[0062] The silica sol and the fiber felt are placed in an aging solution containing a silicon source and allowed to stand for aging.

[0063] The structural strength of the silica sol obtained by hydrolysis and condensation reaction is low. Mixing the silica sol and fiber felt and then subjecting them to aging treatment can promote the full gelation of the silica sol to form a wet silica gel with high structural strength. At the same time, the wet gel can evenly penetrate into the surface of the fiber felt and between the fiber gaps, and tightly bond with the fibers of the fiber felt, which is conducive to obtaining an aerogel composite material with high structural strength and good thermal insulation performance.

[0064] In some embodiments, placing the silica sol and the fiber felt in an aging solution containing a silicon source includes the following steps: mixing the silica sol and the aging solution, and immersing the fiber felt in the aging solution containing the silica sol; or, mixing the silica sol and the fiber felt, and adding the aging solution to immerse the silica sol and the fiber felt.

[0065] In some embodiments, the silicon source in the aging solution includes at least one of tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), butyl orthosilicate (TBOS), and isopropyl orthosilicate (TIOS).

[0066] In some embodiments, the mass fraction of the silicon source in the aging solution is 1% to 20%. As an example, the mass fraction of the silicon source in the aging solution includes, but is not limited to, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18% or 20%.

[0067] In some embodiments, the temperature of static aging is 25° C. to 70° C. As an example, the temperature of static aging includes but is not limited to 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C. or 75° C.

[0068] In some embodiments, the time of static aging is 6 h to 72 h. As an example, the time of static aging includes but is not limited to 6 h, 8 h, 12 h, 16 h, 20 h, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h, 48 h, 52 h, 56 h, 60 h, 64 h, 68 h or 72 h.

[0069] In some embodiments, after the aging treatment, a solvent replacement treatment step is further included. The solvent replacement treatment includes the following steps: placing the wet gel felt in a non-polar solvent, leaving it to stand for 5 minutes to 60 minutes, and then taking it out; repeating the above operation 1 time to 5 times.

[0070] The use of non-polar solvents to replace the wet gel felt can reduce the alcohol hydroxyl content in the wet gel felt and reduce its hydrophilicity, thereby improving the subsequent modification effect and radiation cross-linking effect.

[0071] In some embodiments, the non-polar solvent includes at least one of n-hexane, n-heptane, chloroform, benzene, toluene, xylene, anisole, n-butyl ether and petroleum ether. Further, the non-polar solvent can be n-hexane.

[0072] In some embodiments, the volume ratio of the wet gel felt to the non-polar solvent is 1:(1-4). As an example, the volume ratio of the wet gel felt to the non-polar solvent includes but is not limited to 1:1, 1:2, 1:3 or 1:4.

[0073] In some embodiments, the temperature of the solvent replacement treatment is 25° C. to 60° C. As an example, the temperature of the solvent replacement treatment includes but is not limited to 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C. or 60° C.

[0074] S200: modifying the wet gel felt with a hydrophobic agent, and obtaining a modified gel felt after drying.

[0075] In some embodiments, the wet gel felt is modified by using a hydrophobic agent, comprising the following steps: placing the wet gel felt in a first mixed solution containing the hydrophobic agent for soaking.

[0076] In some embodiments, the hydrophobic agent includes a silane coupling agent containing an alkenyl group.

[0077] The surface of wet gel felt contains a lot of hydrophilic silanol groups, which have poor compatibility with acrylates and are not conducive to the radiation cross-linking reaction. Using silane coupling agents with alkenyl groups for hydrophobic modification can improve the compatibility between wet gel felt and acrylates, increase the reaction rate and grafting rate of radiation cross-linking reaction, and thus improve the hydrophobicity and structural stability of aerogel composite materials.

[0078] In some embodiments, the hydrophobic agent includes vinyl trichlorosilane (molecular formula H2C=CHSiCl3, CAS No. 75-94-5), propenyl trichlorosilane (H2C=CHCH2SiCl3, CAS No. 107-37-9), 2-butenyl trichlorosilane (molecular formula C4H7SiCl3, CAS No. 49749-84-0), 5-hexenyl methyl dichlorosilane (molecular formula C6H 11 At least one of SiCl3, CAS No. 18817-29-3) and 7-octenyltrichlorosilane (molecular formula CH2=CH(CH2)6SiCl3, CAS No. 153447-97-3).

[0079] The hydrophobic agent has good compatibility with acrylate, and the structural characteristics of the straight-chain olefin and polyhalogen substituent make it have less steric hindrance, which is conducive to promoting the rapid progress of the radiation cross-linking reaction.

[0080] In some embodiments, the mass fraction of the silane coupling agent in the first mixed solution is 5% to 40%. As an example, the mass fraction of the silane coupling agent in the first mixed solution includes but is not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0081] In some embodiments, the solvent of the first mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane. Further, the solvent of the first mixed liquid may be ethanol.

[0082] In some embodiments, the soaking conditions include: soaking at 25°C to 70°C for 12h to 72h. As an example, the soaking temperature includes but is not limited to 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, and the soaking time includes but is not limited to 12h, 18h, 24h, 30h, 36h, 42h, 48h, 54h, 60h, 66h or 72h.

[0083] In some embodiments, during the soaking process, the first mixed solution is continuously stirred to improve the uniformity of the hydrophobic modification.

[0084] S300: A protective layer is formed on the modified gel felt using acrylic acid to obtain a composite gel felt.

[0085] The use of acrylate to form a protective layer on the modified gel felt can form a dense three-dimensional cross-linked network structure after radiation cross-linking, giving the aerogel composite material better hydrophobic properties and effectively improving its flexibility and toughness.

[0086] In some embodiments, forming a protective layer on the modified gel felt using acrylate includes the following steps: spraying the modified gel felt with a second mixed liquid containing acrylate to form the protective layer.

[0087] In some embodiments, the acrylate includes at least one of methyl acrylate (MA), butyl acrylate (BA), methyl methacrylate (MMA), pentaerythritol tetraacrylate (PET4A), hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), hydroxyethyl methacrylate (HEMA), hydroxypropyl methacrylate (HPMA), ethylene glycol dimethacrylate (EGDMA) and trimethylolpropane triacrylate (TMPTA). Further, the acrylate includes at least one of methyl acrylate (MA) and trimethylolpropane triacrylate (TMPTA).

[0088] In some embodiments, the mass fraction of acrylate in the second mixed solution is 3% to 40%. As an example, the mass fraction of acrylate in the second mixed solution includes but is not limited to 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0089] In some embodiments, the solvent of the second mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane.

[0090] In some embodiments, the thickness of the protective layer is 10 μm to 3000 μm. As an example, the thickness of the protective layer includes but is not limited to 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 200 μm, 500 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm, 1800 μm, 2000 μm, 2200 μm, 2500 μm, 2800 μm or 3000 μm.

[0091] S400: performing radiation cross-linking treatment on the composite gel felt, and obtaining an aerogel composite material after drying.

[0092] It can be understood that the radiation cross-linking technology is to use a high-energy radiation source (gamma rays, X-rays and electron beams, etc.) to irradiate organic materials, so that the molecular chains inside the material are broken and reorganized to form a new cross-linked structure. The present application uses radiation cross-linking treatment to induce cross-linking between alkenyl-containing silane coupling agents and acrylates, thereby enhancing the mechanical strength and structural stability of the aerogel composite material, effectively improving its durability and impact resistance, and helping to suppress the powdering problem of the aerogel composite material during transportation, construction and use, ensuring its safety and convenience during use.

[0093] In some embodiments, the radiation source for the radiation cross-linking treatment includes at least one of a γ-ray source, an X-ray source, and an electron beam source. Further, the radiation source for the radiation cross-linking treatment may be a γ-ray source. Further, the γ-ray source includes a radioactive isotope, such as cobalt-60 ( 60 Co) and cesium-137 ( 137 Cs).

[0094] In some embodiments, the conditions of the radiation cross-linking treatment include: the radiation dose is 50 kGy to 600 kGy. As an example, the radiation dose includes but is not limited to 50 kGy, 100 kGy, 150 kGy, 200 kGy, 250 kGy, 300 kGy, 350 kGy, 400 kGy, 450 kGy, 500 kGy, 550 kGy or 600 kGy.

[0095] In some embodiments, in step S400, after the radiation cross-linking treatment, the drying treatment includes at least one of supercritical drying, freeze drying and atmospheric pressure drying. The supercritical drying may be supercritical CO2 drying or supercritical ethanol drying.

[0096] In some embodiments, in step S400, after the radiation cross-linking treatment, the drying treatment adopts supercritical drying. Through supercritical drying, the solvent in the composite material can be effectively removed, and the structural stability of the aerogel can be maintained, and the high porosity and superhydrophobicity characteristics of the aerogel can be maintained, thereby obtaining an aerogel composite material with excellent performance.

[0097] In a second aspect of the present application, an aerogel composite material is provided, which is prepared by the above-mentioned preparation method of the aerogel composite material.

[0098] In a third aspect of the present application, a thermal insulation material is provided, comprising the above-mentioned aerogel composite material.

[0099] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0100] Example 1

[0101] The preparation method of the aerogel composite material of this embodiment is as follows:

[0102] (1) Preparation of silica sol: Ethyl orthosilicate, anhydrous ethanol and water were mixed evenly in a molar ratio of 1:3:12; nitric acid was added to adjust the pH to 5 and hydrolyzed for 1 h; ammonia water was added to adjust the pH to 8 and polycondensed for 1 h to obtain silica sol.

[0103] (2) Preparation of wet gel felt: The silica sol was placed in an aging solution, and a glass fiber felt with a thickness of 1 mm was added, and the solution was aged at 30°C for 48 h to obtain a wet gel felt. The aging solution was an ethanol solution of tetraethyl orthosilicate (TEOS), and the mass fraction of TEOS was 10%.

[0104] (3) Solvent replacement of wet gel felt: Place the wet gel felt in n-hexane and soak it for 10 minutes. After soaking, take it out and replace it with new n-hexane and soak it again for 10 minutes. Repeat three times.

[0105] (4) Preparation of modified gel felt: The wet gel felt after solvent replacement was placed in the first mixed solution and soaked at 30°C for 36 hours to obtain a modified gel felt. The first mixed solution was a n-hexane solution of vinyltrichlorosilane with a mass fraction of 25%.

[0106] (5) Preparation of composite gel felt: Spray the second mixed liquid on the surface of the modified gel felt to form a protective layer with a thickness of 500 μm to obtain a composite gel felt. The second mixed liquid is an ethanol solution of methyl acrylate (MA), and the mass fraction of MA is 25%.

[0107] (6) Preparation of aerogel composite materials: The composite gel felt was subjected to radiation cross-linking treatment using cobalt-60 as a gamma ray source with an irradiation dose of 80 kGy, and then supercritical CO2 drying was performed to obtain an aerogel composite material.

[0108] Embodiments 2 to 9

[0109] The preparation methods of the aerogel composite materials of Examples 2 to 11 are basically the same as the preparation method of the aerogel composite material of Example 1, and the specific differences are as follows:

[0110] Embodiment 2: The silane coupling agent is acryltrichlorosilane.

[0111] Example 3: In the first mixed solution, the mass fraction of vinyltrichlorosilane is 5%.

[0112] Example 4: In the first mixed solution, the mass fraction of vinyltrichlorosilane is 40%.

[0113] Example 5: The soaking time of the wet gel felt in the first mixed solution is 12 hours.

[0114] Example 6: The soaking time of the wet gel felt in the first mixed solution is 72 hours.

[0115] Example 7: Trimethylolpropane triacrylate (TMPTA) is used as the acrylate.

[0116] Embodiment 8: The thickness of the protective layer is 100 μm.

[0117] Embodiment 9: The thickness of the protective layer is 1000 μm.

[0118] Comparative Examples 1 to 3

[0119] The preparation methods of the aerogel composite materials of Comparative Examples 1 to 3 are basically the same as the preparation method of the aerogel composite material of Example 1, and the specific differences are as follows:

[0120] Comparative Example 1: Steps (3) to (6) are not performed, and the wet gel felt obtained in step (2) is dried with supercritical CO2 to obtain an aerogel composite material.

[0121] Comparative Example 2: Step (4) is not performed, and the wet gel felt obtained in step (3) is sprayed with the second mixed solution, and then subjected to radiation crosslinking and supercritical CO2 drying to obtain an aerogel composite material.

[0122] Comparative Example 3: Step (5) is not performed, and the modified gel felt obtained in step (4) is subjected to radiation crosslinking and supercritical CO2 drying to obtain an aerogel composite material.

[0123] Test Case

[0124] The following tests were performed on the aerogel composite materials of each embodiment and each comparative example:

[0125] (1) Thermal conductivity: refer to GB / T34336-2017 Nanoporous aerogel composite insulation products.

[0126] (2) Hydrophobicity: refer to GB / T34336-2017 Nanoporous Aerogel Composite Insulation Products.

[0127] (3) Bending times: Fold the aerogel composite material 90° along the long axis and restore it within 3 seconds, and observe whether there are cracks or breaks at the folded part. If cracks or breaks are found, the last folding number is recorded as the bending times of the aerogel composite material. The maximum number of folding times is 50.

[0128] (4) Powder loss rate: The aerogel composite material was placed on a vibrating shaker and vibrated for 10 min. The relative percentage of the mass difference before and after vibration to the mass before vibration was recorded as the powder loss rate.

[0129] The above test results are shown in Table 1 below:

[0130] Table 1. Performance test results of aerogel composites

[0131]

[0132] As shown in Table 1, the thermal conductivity of the aerogel composite materials prepared in Examples 1 to 9 is 0.030W / (m·K)~0.038W / (m·K), the hydrophobicity is 95.23%~97.58%, the number of bending resistance is more than 50 times, and the powder loss rate is 1%~5%. Among them, as the amount of hydrophobic agent increases, the better the radiation cross-linking effect, the better the hydrophobicity, the stronger the bending resistance, the lower the powder loss rate, and the higher the thermal conductivity; similarly, as the amount of acrylate spraying increases, the higher the radiation cross-linking effect, the hydrophobicity does not change much, the stronger the bending resistance, the lower the powder loss rate, and the higher the thermal conductivity.

[0133] The hydrophobicity, bending resistance and anti-powdering performance of the aerogel composite materials prepared in Examples 1 to 9 are significantly better than those of the aerogel composite materials prepared in Comparative Examples 1 to 3, indicating that the aerogel composite materials prepared in the present application have high thermal insulation, super hydrophobicity, good anti-powdering performance and excellent toughness, and the overall stability and performance are significantly improved.

[0134] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0135] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for preparing an aerogel composite material, characterized in that: The following steps are involved: Mixing silica sol and fiber felt, and performing aging treatment to obtain wet gel felt; Modifying the wet gel felt by using a hydrophobic agent to obtain a modified gel felt; forming a protective layer on the modified gel felt using acrylic acid to obtain a composite gel felt; The composite gel felt is subjected to radiation cross-linking treatment and dried to obtain the aerogel composite material.

2. The method for preparing an aerogel composite material according to claim 1, characterized in that: The hydrophobic agent includes at least one of vinyl trichlorosilane, propenyl trichlorosilane, 2-butenyl trichlorosilane, 5-hexenyl methyl dichlorosilane and 7-octenyl trichlorosilane.

3. The method for preparing the aerogel composite material according to claim 1, characterized in that: The acrylic acid ester includes at least one of methyl acrylate, butyl acrylate, methyl methacrylate, pentaerythritol tetraacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylene glycol dimethacrylate and trimethylolpropane triacrylate.

4. The method for preparing an aerogel composite material according to any one of claims 1 to 3, characterized in that: The wet gel felt is modified by using a hydrophobic agent, comprising the following steps: The wet gel felt is placed in a first mixed liquid containing the hydrophobic agent for soaking.

5. The method for preparing an aerogel composite material according to claim 4, characterized in that: At least one of the following conditions is met: (1) The mass fraction of the hydrophobic agent in the first mixed liquid is 5% to 40%; (2) the solvent of the first mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane; (3) The soaking treatment conditions include: soaking at 25°C to 70°C for 12h to 72h.

6. The method for preparing an aerogel composite material according to any one of claims 1 to 3, characterized in that: Forming a protective layer on the modified gel felt using acrylic acid comprises the following steps: The modified gel felt is sprayed with a second mixed liquid containing the acrylic ester to form a protective layer.

7. The method for preparing an aerogel composite material according to claim 6, characterized in that: At least one of the following conditions is met: (1) The mass fraction of the acrylic acid ester in the second mixed liquid is 3% to 40%; (2) the solvent of the second mixed liquid includes at least one of methanol, ethanol, isopropanol, n-propanol, acetone, n-hexane and n-heptane; (3) The thickness of the protective layer is 10 μm to 3000 μm.

8. The method for preparing an aerogel composite material according to any one of claims 1 to 3, characterized in that: Mixing silica sol and fiber felt and performing an aging reaction includes the following steps: Mixing a silicon source, an organic solvent and water, and performing a hydrolysis reaction and a polycondensation reaction to obtain the silica sol; The silica sol and the fiber felt are placed in an aging solution containing a silicon source and allowed to stand for aging.

9. An aerogel composite material, characterized in that: The aerogel composite material is prepared by the preparation method of any one of claims 1 to 8.

10. A heat insulation material, characterized in that: The aerogel composite material comprises the aerogel composite material according to claim 9.

Citation Information

Cited By

  • Encapsulated aerogel composite material and preparation method thereof

    CN121377730A